Uji Iritasi dan Aktivitas Penumbuh Rambut Hair Tonic dari Tanaman Usada Bali pada Mencit - Putu Era Sandhi Kusuma Yuda; Puguh Santoso; Erna Cahyaningsih; Gusti Ayu Made Indah Siantari (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
The existence of side effects from drugs used for hair loss treatment urges the need for safer alternatives, especially from natural ingredients. The purpose of this study was to determine the effectiveness and safety of hair tonic from Usada Bali (containing Polycias scutellaria, Hibiscus tiliaceus, Trigonella foenum graecum, and Cananga odorata) in mice. Experimental animals were divided into four groups: negative control was given a carrier fluid, positive control was given hair tonic on the market, and the treatment group was given hair tonic with simplicia concentration of 10% and 20%. Hair length was measured on days 7 and 21 with the treatment given daily topically on the backs of shaved mice. The irritation test was carried out at 24 and 48 hours. The data obtained were tested statistically by ANOVA test followed by Tukey's test with 95% confidence level. The results showed that the hair tonic formula contained alkaloids, flavonoids, saponins, tannins and triterpenoids. The irritation test did not show any irritation on the skin of the mice. The hair growth activity test of the herbal hair tonic formula combination of Polycias scutellaria leaf, Hibiscus tiliaceus leaf, Trigonella foenum graecum seed and Cananga odorata flower showed significantly faster hair growth than the negative control at both concentrations and not significantly different from the positive control. This hair tonic formula has the potential to be developed into a natural hair growth agent without irritation to the skin.